PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 005 SIKAKAK KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI - Libarti Libarti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study began with the results of science learning for third grade students of SD Negeri 005 Sikakak,Kecamatan Cerenti, Kabupaten Kuantan Singingi which was still low. The purpose of this study is to improvestudent learning outcomes. The design of this study uses classroom action research (CAR) consisting of twocycles. The subjects of this study were third grade students with a total of 20 students. The results of the studystated that teacher activity in the first cycle obtained a percentage of 75%. At the second meeting increased to79.16%. While in the second cycle at the first meeting reached 87.5%, and at the second meeting increased to91.66%. Student activity in cycle I gained a percentage of 66.6%. At the second meeting increased to 75%.Whereas in the second cycle, at the first meeting it reached 83.3%, and at the second meeting increased to87.5%. Learning outcomes on the baseline score were 40% with incomplete categories, in cycle I, it increased to70% in the complete category and in cycle II it increased to 90% in the complete category. Based on the findingsabove, it can be concluded that, the application of inquiry learning models can improve science learningoutcomes for third grade students of SD Negeri 005 Sikakak, Kecamatan Cerenti, Kabupaten Kuantan Singingi.